Connect with knowledgeable experts and enthusiasts on IDNLearn.com. Join our community to receive prompt, thorough responses from knowledgeable experts.
Sagot :
Let's solve the given problem step by step.
We are given the function [tex]\( f(g(x)) = \frac{4x^2 - 9}{3} \)[/tex] and we need to find [tex]\( f(g(6)) \)[/tex].
First, we need to find the value of [tex]\( g(6) \)[/tex]. Let's assume that the function [tex]\( g(x) \)[/tex] is defined as:
[tex]\[ g(x) = \frac{x^2 - 7x + 10}{2} \][/tex]
We need to substitute [tex]\( x = 6 \)[/tex] in [tex]\( g(x) \)[/tex] to find [tex]\( g(6) \)[/tex]:
[tex]\[ g(6) = \frac{6^2 - 7 \cdot 6 + 10}{2} \][/tex]
[tex]\[ g(6) = \frac{36 - 42 + 10}{2} \][/tex]
[tex]\[ g(6) = \frac{4}{2} \][/tex]
[tex]\[ g(6) = 2 \][/tex]
Now, we plug [tex]\( g(6) \)[/tex] into [tex]\( f(x) \)[/tex] to find [tex]\( f(g(6)) \)[/tex], which means we need to find [tex]\( f(2) \)[/tex] since [tex]\( g(6) = 2 \)[/tex].
So we substitute [tex]\( x = 2 \)[/tex] into the function [tex]\( f(x) \)[/tex]:
[tex]\[ f(x) = \frac{4x^2 - 9}{3} \][/tex]
Substitute [tex]\( x = 2 \)[/tex]:
[tex]\[ f(2) = \frac{4 \cdot 2^2 - 9}{3} \][/tex]
[tex]\[ f(2) = \frac{4 \cdot 4 - 9}{3} \][/tex]
[tex]\[ f(2) = \frac{16 - 9}{3} \][/tex]
[tex]\[ f(2) = \frac{7}{3} \][/tex]
[tex]\[ f(2) = 2.3333333333333335 \][/tex]
Therefore, [tex]\( f(g(6)) = 2.3333333333333335 \)[/tex].
So the final answer is:
[tex]\[ f(g(6)) = 2.3333333333333335 \][/tex]
We are given the function [tex]\( f(g(x)) = \frac{4x^2 - 9}{3} \)[/tex] and we need to find [tex]\( f(g(6)) \)[/tex].
First, we need to find the value of [tex]\( g(6) \)[/tex]. Let's assume that the function [tex]\( g(x) \)[/tex] is defined as:
[tex]\[ g(x) = \frac{x^2 - 7x + 10}{2} \][/tex]
We need to substitute [tex]\( x = 6 \)[/tex] in [tex]\( g(x) \)[/tex] to find [tex]\( g(6) \)[/tex]:
[tex]\[ g(6) = \frac{6^2 - 7 \cdot 6 + 10}{2} \][/tex]
[tex]\[ g(6) = \frac{36 - 42 + 10}{2} \][/tex]
[tex]\[ g(6) = \frac{4}{2} \][/tex]
[tex]\[ g(6) = 2 \][/tex]
Now, we plug [tex]\( g(6) \)[/tex] into [tex]\( f(x) \)[/tex] to find [tex]\( f(g(6)) \)[/tex], which means we need to find [tex]\( f(2) \)[/tex] since [tex]\( g(6) = 2 \)[/tex].
So we substitute [tex]\( x = 2 \)[/tex] into the function [tex]\( f(x) \)[/tex]:
[tex]\[ f(x) = \frac{4x^2 - 9}{3} \][/tex]
Substitute [tex]\( x = 2 \)[/tex]:
[tex]\[ f(2) = \frac{4 \cdot 2^2 - 9}{3} \][/tex]
[tex]\[ f(2) = \frac{4 \cdot 4 - 9}{3} \][/tex]
[tex]\[ f(2) = \frac{16 - 9}{3} \][/tex]
[tex]\[ f(2) = \frac{7}{3} \][/tex]
[tex]\[ f(2) = 2.3333333333333335 \][/tex]
Therefore, [tex]\( f(g(6)) = 2.3333333333333335 \)[/tex].
So the final answer is:
[tex]\[ f(g(6)) = 2.3333333333333335 \][/tex]
We value your presence here. Keep sharing knowledge and helping others find the answers they need. This community is the perfect place to learn together. Thank you for visiting IDNLearn.com. For reliable answers to all your questions, please visit us again soon.